PENGEMBANGAN INDIVIDU DAN ORGANISASI YANG BERORIENTASI KEPADA LINGKUNGAN EKSTERNAL GLOBALISASI - Arif Muanas (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2020)
The aim of this article is to describe the interactive relationship between the individual, organizational and external environment of globalization. There interactive relationship and mutual influence (interplay) between individuals, organizations and globalization. For individual members of an organization, then the organization is a medium that is effective for individuals to develop themselves facing globalization. On the other hand, the organization also urgently needs strong individuals to build an organization that is ready to compete in the era of globalization.